Preparação e caracterização estrutural de aerogéis de sílica com diferentes concentrações de F127 - Fermino, Tainá Zampieri [UNESP] (2014)
The present work aims to study the effects of varying the concentration of the copolymer tri-block (F127 Pluronic) in the preparation of silica gels from acid hydrolysis of tetraethylorthosilicate (TEOS), through its structural features in stages ranging from the saturated (wet gels) to dry gel state (aerogels and xerogels). The F127 is a micelle forming polymer as used in the impregnator structure of the pore-forming species-process silica because the micellar structure of F127 can determine the formation of pores of different sizes during the process of gelation on hydrolysis and polycondensation to obtain porous bodies, producing interesting structures of porous silica obtained by sol-gel method. Silica aerogels were obtained by ambient pressure drying (APD) after silylation of the gels in humid phase. The process of silylation was done in the wet gels using 20% by volume of hexamethyldisilazane (HMDZ) in n-hexane. Heat treatment at 300, 500, 700 e 900 ºC was performed in order to characterize. The structure of aerogels by APD with different compositions of F127. This characterization was carried out using nitrogen adsorption and small angle X-ray scattering techiniques. Additionally xerogels having the same compositions F127 were obtained by aging in a solution of 0.1 M NH4OH and APD. The wet gels showed a mass fractal structure with fractal dimension D around 2.1 and fractal characteristic size of the domain (ξ) goes from 9.05 for gel prepared without the addition of F127 to values that exceed the maximum experimental limit of 14.2 nm with increasing concentration of F127. These gels also exhibit a fractal structure that permeate the field of fractal structure of the main mass of wet gels. Nitrogen adsorption shows a specific surface area (SBET) for APD aerogels, which presented a value of around 800 m2/g to different concentrations of F127, the volume (Vp), the average length (lp) pores of aerogels increased more or less regular...